1998
DOI: 10.3354/dao032151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Vibrio harveyi infections in Penaeus vannamei larvae

Abstract: ABSTRACT. A culture of Vibrio harveyi, isolated from diseased Penaeus vannamei, was pathogenic in penaeid shrimp larvae when used in a bath at 105 cells n~l-' for 2 h. The resultant disease had characteristics of Bolitas negricans, as observed in Ecuadorian hatcheries, namely the development of bioluminescence, reduced feeding and retarded development, sluggish swimming, reduced escape mechanisms, degeneration of hepatopancreatic tissue with resultant formation of necrotic bundles, and increased mortality. Koc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 9 publications
2
77
0
5
Order By: Relevance
“…On the other hand, a noticeable potent growth inhibition (MIC = 0.3 -0.6 mM for Pen-3a) associated with slow killing of the target bacteria (10% of bacteria are still alive after a 24-h incubation) was observed on Aerococcus 6iridans, which is reported to be highly pathogenic in crabs and lobsters, in which it induces rapid septicemia and subsequent death [37]. Finally, penaeidins were found to display little activity against Gram-negative strains, including the Vibrio species commonly responsible for many crustacean bacterial infections [38,39]. Despite better efficiency of Pen-3a on most of the strains tested, similar activity spectra and inhibition mechanisms are observed for both Pen-2 and -3a (at concentrations above the MIC, sensitive strains are killed or inhibited with identical time courses).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…On the other hand, a noticeable potent growth inhibition (MIC = 0.3 -0.6 mM for Pen-3a) associated with slow killing of the target bacteria (10% of bacteria are still alive after a 24-h incubation) was observed on Aerococcus 6iridans, which is reported to be highly pathogenic in crabs and lobsters, in which it induces rapid septicemia and subsequent death [37]. Finally, penaeidins were found to display little activity against Gram-negative strains, including the Vibrio species commonly responsible for many crustacean bacterial infections [38,39]. Despite better efficiency of Pen-3a on most of the strains tested, similar activity spectra and inhibition mechanisms are observed for both Pen-2 and -3a (at concentrations above the MIC, sensitive strains are killed or inhibited with identical time courses).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Karunasagar et al (1994) señalaron una menor sobrevivencia en los subestadios larvarios de P. monodon cuando fueron infectados con una cepa de V. harveyi resistente a cloranfenicol y eritromicina, comparados con aquellos que fueron infectados con una cepa silvestre de V. harveyi (dosis de 10 3 y 10 5 UFC/ml, respectivamente). Robertson et al (1998) reportaron infección en los subestadios larvarios de L. vannamei con V. harveyi a una dosis de 10 5 UFC/ml, la cual fue capaz de producir bioluminicencia y una enfermedad larval denominada como bolitas negras. Por otra parte, Kannapiran et al (2009) y SotoRodríguez et al (2012 sugirieron que V. harveyi es responsable de diversos problemas en camarón, siendo el síndrome de enfermedad de las patas rojas uno de ellos.…”
Section: Resultados Y Discusiónunclassified
“…Las especies que conforman al género Vibrio, originan trastornos a las larvas de camarón, los cuales pueden llevar a la muerte de las mismas (Widanarni et al, 2003;Austin y Zhang, 2006;Ravi et al, 2007). Al infectar subestadios larvales de L. vannamei con V. harveyi (10 5 UFC/ml), Robertson et al (1998) determinaron que esta dosis fue suficiente para generar el trastorno conocido como bolitas negras, cuyos síntomas son degradación de tejido hepatopáncreatico, nado lento, reducción en la alimentación, y retardo en el desarrollo larval, además de la bioluminiscencia que puede llegarse a percibir con esta especie de Vibrio. Estos trastornos pudieron propiciar la mortalidad de los subestadios larvarios empleados es esa investigación.…”
Section: Introductionunclassified
“…Bowser et al (1981) reported vacuole formation in hepatopancreas which resulted after the intra-hemocoelic injection of Vibrio spp. Pathogenecity of Vibrio harveyi was studied by Robertson et al (1998) in Penaeus vannamei larvae and the results showed necrotic bundles in hepatopancreas of the infected animal. The present study also supports previous studies with necrotic bundles found scattered throughout the hepatopancreas of the shell-diseased N. mederi.…”
Section: Discussionmentioning
confidence: 99%